Application of E‐technologies for regional development: The case of Vilnius city - Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras; Banaitis, Audrius (Journal of Business Economics and Management, 2010)
The investigation carried out by the authors of this paper under “Intelligent Cities” (Framework 6 programme) and e‐City (Phare PPF) projects helped to identify and describe major trends of e‐cities development in industrialized countries as well as providing recommendations for e‐Vilnius development. Research included the following four stages: comparative description of the e‐cities development in developed countries and in Vilnius, comparison and contrast of e‐cities development in developed countries and in Vilnius, development of some of the general recommendations as how to improve the efficiency levels for e‐Vilnius, submission of particular recommendations for e‐Vilnius. In order to throw more light on the Model, a more detailed description of some above stages follows in the paper. Elektroninių technologijų taikymas regioninėje plėtroje: Vilniaus miesto pavyzdys Santrauka. Šio straipsnio autorių atliktas tyrimas pagal projektus „Protingi miestai“ (6-oji bendroji programa) ir „E.miestas“ (Phare PPF) padėjo nustatyti bei aprašyti pagrindines kryptis, leidžiančias plėtoti e. miestus industrializuotose šalyse, ir pateikti elektroninės Vilniaus plėtros rekomendacijas. Tyrimą sudaro keturios pakopos: lyginamojo e. miestų plėtojimo išsivysčiusiose šalyse ir Vilniuje aprašymas, e. miestų plėtojimo išsivysčiusiose šalyse ir Vilniuje sugretinimas bei skirtumų tarp jų parodymas, bendrųjų rekomendacijų, kaip pakelti e. Vilniaus plėtros efektyvumą, sukūrimas ir sukurtų rekomendacijų pateikimas. Kad svarstomas modelis būtų aiškesnis, pateikiamas išsamesnis kai kurių pakopų aprašymas. Reikšminiai žodžiai: protingi miestai, e. Vilnius, modeliavimas, 6-oji bendroji programa. First Published Online: 10 Feb 2011